The Mediating Role of Job Satisfaction in the Effect of Perceived Organizational Support on Organizational Commitment - Ni Wayan Andini Febriyanti; I Gede Riana (International Journal of Economics, Management and Accounting, 2025)
This research investigates the influence of perceived organizational support on organizational commitment, with job satisfaction serving as a mediating variable. The study was carried out at the Regional Development Planning Agency (Bappeda) of Gianyar Regency, using a purposive sampling method to select 49 participants. A survey approach was adopted, employing both questionnaires and interviews as data collection tools. Data were analyzed using descriptive statistics and inferential analysis, specifically path analysis. The findings reveal that perceived organizational support positively and significantly influences organizational commitment. Additionally, perceived organizational support has a positive and significant relationship with job satisfaction. Job satisfaction, in turn, also positively and significantly affects organizational commitment. Moreover, job satisfaction is found to mediate the relationship between perceived organizational support and organizational commitment. Theoretically, the study contributes to the understanding of social exchange theory in the context of organizational behavior. Practically, it offers insights into how enhancing perceived organizational support and fostering job satisfaction can improve employees’ commitment to the organization. The research underscores the importance of managing these two factors to strengthen organizational commitment.